Geochemistry and geochronology of basic igneous rocks in Bairin Right banner, southeastern inner Mongolia, China: Implications for the final closure of the Paleo—Asian Ocean along the Xar Moron suture zone - Yang, Wenpeng; Li, Chenglu; Alam, Masroor; Fu, Anzong; Zheng, Bo; Yang, Yuanjiang; Hu, Xiaofang (Frontiers in Earth Science, 2023)
This paper reports first discovery of basic igneous rocks in the Bairin Right Banner in Southeastern Inner Mongolia, China. LA-ICP-MS zircon U-Pb concordant mean ages of massive basalt, diabase and pillow basalt are 272.0 ± 2.8 Ma, 261.5 ± 3.2 Ma and 256.5 ± 2.5 Ma, respectively, suggesting their formation during the Late Permian. The massive basalt, diabase and pillow basalt are tholeiitic with low Mg# values in the ranges of 46.2-66.8, 54.4-71.0 and 53.5-58.2, respectively. They have similar chondrite-normalized rare earth element (REE) patterns. The intensity of REE differentiation is similar to that of typical enriched mid-ocean ridge basalts (E-MORB). The pillow basalts are relatively enriched in Ba and U, while slightly depleted in Rb and Th, and show geochemical affinity to E-MORB. The massive basalts and diabases have the same primitive mantle-normalized patterns, and are relatively enriched in Rb, Ba and U, while depleted in Nb and Ta, similar to the typical island arc magmas. Our new findings indicate that the intra-oceanic subduction of the Paleo-Asian Oceanic slab was still going on during the late Permian in the Bairin Right Banner area and combined with the previous studies, it might have been closed during the Late Permian to Early Triassic along the Xar Moron suture zone.